Investigasi Kualitas Hidup Pasien Hemodialisa Berdasarkan Aspek Dukungan Keluarga - Haiya, Nutrisia Nu'im; Ardian, Iwan; Azizah, Intan Rismatul; Marfu'ah, Siti (Jurnal Gema Keperawatan, 2024)
Patients with end-stage kidney disease require hemodialysis, which is a replacement for kidney function. Continuous hemodialysis therapy has a psychological impact and an impact on quality of life. Changes in the quality of life of hemodialysis patients are influenced by many factors, one of which is family support. Family support is needed in holistic nursing services so that patients remain motivated and maintain their physical and psychological condition, even though they are dependent on hemodialysis therapy. This study aimed to obtain an overview of the quality of life of hemodialysis patients based on aspects of family support. The research design was cross-sectional with a total sampling technique of 41 respondents. The inclusion criteria were hemodialysis patients who had undergone hemodialysis 3 times, a family waiting for them, and those who experienced decreased consciousness. The variables measured were family support and quality of life using the WHOQOL-BREF (WHO Quality of Life Breef) questionnaire instrument, analyzed using the gamma test. The majority of hemodialysis patients were men (65,9%) aged 45-55 years or early elderly (36,6%) working in the private sector (26,8%) with a hemodialysis duration of 1–3 years (73,2%) with a program 2 times per week (97.6%), accompanied by chronic illness (65,9%), and living with husband or wife (68,3%). Family support had a significant effect on the quality of life of hemodialysis patients (p= 0,012 and r =1,000, respectively). The better the family support, the better the quality of life of hemodialysis patients.